Does phonological overlap of cognate words modulate cognate acquisition and processing in developing and skilled readers?. (2nd October 2018) - Valente, Daniela; Ferré, Pilar; Soares, Ana; Rato, Anabela; Comesaña, Montserrat
ABSTRACT: Very few studies exist on the role of cross-language similarities in cognate word acquisition. Here we sought to explore, for the first time, the interplay of orthography (O) and phonology (P) during the early stages of cognate word acquisition, looking at children and adults with the same level of foreign language proficiency and by using two variants of the word-association learning paradigm (auditory learning method vs. auditory + written method). Eighty participants (40 children and 40 adults, native speakers of European Portuguese [EP]), learned a set of EP-Catalan cognate words and noncognate words. Among the cognate words, the degree of orthographic and phonological similarity was manipulated. Half of the children and adult participants learned the new words via an L2 auditory and written-L1 word association method, while the other half learned the same words only through an L2 auditory-L1 word association method. Both groups were tested in an auditory recognition task and a go/no-go lexical decision task. Results revealed a disadvantage for children in comparison to adults, which was reduced in the auditory learning method. Furthermore, there was an advantage for cognates relative to noncognates regardless of the age of participants. Importantly, there were modulations in cognate word processing as a function of the degree of O and P overlap that were restricted to children. The findings are discussed in light of the most relevant bilingual models of word recognition.